The Cambridge companion to the sonnet - Cousins, A. D. (Cambridge companions to topics., 2011)
"Beginning with the early masters of the sonnet form, Dante and Petrarch, the Companion examines the reinvention of the sonnet across times and cultures, from Europe to America. In doing so, it considers sonnets as diverse as those by William Shakespeare, William Wordsworth, George Herbert and e. e. cummings. The chapters explore how we think of the sonnet as a 'lyric' and what is involved in actually trying to write one. The book includes a lively discussion between three distinguished contemporary poets - Paul Muldoon, Jeff Hilson and Meg Tyler - on the experience of writing a sonnet, and a chapter which traces the sonnet's diffusion across manuscript, print, screen and the internet. A fresh and authoritative overview of this major poetic form, the Companion expertly guides the reader through the sonnet's history and development into the global multimedia phenomenon it is today"--